A comparative study of different adjuncts to enhance the effects of intrathecal bupivacaine - Sur, Debajyoti; Agarwal, Archana; Chaudhary, Ajay Kumar; Bogra, Jaishri; Singh, Prithvi Kumar; Gupta, Rajni; Bhatia, Vinod Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Spinal anaesthesia is the commonly used technique for lower abdominal surgeries. Adjuvants to bupivacaine have been used to provide good quality of perioperative and postoperative analgesia. The aim of the study was to evaluate the effects of subarachnoid administration of bupivacaine with clonidine, magnesium, dexmedetomidine and saline group. Methods: The prospective, comparative single blind study included 120 patients in American society of anaesthesiologist (ASA) grade I and II, scheduled for lower abdominal surgeries were allocated in four groups. Each group included 15 mg bupivacaine with various adjuvants (30 µg clonidine, 50 mg magnesium sulphate and 3µg dexmedetomidine) were compared with saline group (group S). Results: Time of onset was earlier in groups D and C but delayed in group M. The total power regains (B0) in group D (250.8±18.87), group M (235.23±24.66) and group C (242.70±25.98) were significantly delayed (p<0.05) as compare with group S (180.07±18.53). Demand of analgesia was significantly earlier in group S as compared with groups C, M and D. Similarly, the time of two segment regression was significantly earlier in group S as compared with groups C, M and D (p<0.001). Patients were hemodynamically stable in groups D, C and M as compared to Group S. Conclusions: Dexmedetomidine and clonidine were equally effective and better as compared to magnesium as an adjunct to intrathecal bupivacaine.